Vitamin D status in relation to age, bone mineral density of the spine and femur in obese Saudi females - A hospital-based study - Tarfa Ibrahim Albrahim; Manal Abdulaziz Binobead (Elsevier, 2019)
The aim of the present study was to evaluate the association between Bone mineral density in lumber spine and femoral neck with serum total levels of vitamin D, sun exposure and Consumption of vitamin D Supplement in obese Saudi females aged between 30 and 54 years old. Recent attention to the high prevalence of osteoporosis and its association with low vitamin D levels in adults has raised the importance of vitamin D evaluation. A low level of vitamin D is considered to be one of the most important risk factors for osteoporosis. In this study; 120 obese Saudi females with no diagnosed chronic diseases attending the Outpatient clinic at king Khalid University hospital in Riyadh. Saudi Arabia, recruited randomly in period of 12 months. In this study, Serum levels of total Vitamin D were considered to be severe deficient if it was lower than 25 ng/mL, mild to moderate deficient if it was between 25 and 60 ng/mL and optimum level if it was 61-200 ng/mL. The results showed that; sun exposure was significantly affect and Correlate with serum level of Vitamin D in the subjects. In addition, daily consumption of Vitamin D supplement was significantly affect and Correlate with serum level of Vitamin D in the subjects of this study. Moreover, the results showed that; 50% of the age group (40-49 years old) having severe deficiency of Vitamin D. While, 50% of the age group (50-59 years old) having optimal level of Vitamin D. And these results mean that age is not Correlated with vitamin D deficiency in subjects of this study. Keywords: Vitamin D, Secosteroids, 25-Hydroxyergocalciferol, Calcifediol, Osteoporosis, Osteopenia